STRATEGI GENERASI MUDA DALAM MENGINJIL: BERKACA PADA TELADAN PARA MISIONARIS DALAM SEJARAH GEREJA INDONESIA - Hermanto, Yanto Paulus; Alexander, Christopher; Christi, Joseph Patria; Napitupulu, Tina Natalia; Gracia, Jeremy Deo (Sekolah Tinggi Teologi Injili Abdi Allah, 2021)
AbstractThe lack of awareness of the young generation towards evangelism needs to be addressed. As Indonesia will enter the demographic bonus period in 2030-2040, Christianity also needs to take advantage of this opportunity to spread the gospel of the Lord Jesus Christ. Therefore, the young generation needs to prepare themselves to be able to do evangelism effectively, one of which is by understanding evangelism strategies. On this occasion, the author raised the title